The GRACE Scale in the Prognosis of Patients with Takotsubo Syndrome - Malgorzata Zalewska-Adamiec; Lukasz Kuzma; Slawomir Dobrzycki; Hanna Bachorzewska-Gajewska (Journal of Interventional Cardiology)
Background. The prognosis of Takotsubo syndrome (TTS) is comparable to that of the non-ST-elevation myocardial infarction (NSTEMI). The GRACE scale is used to assess the risk of premature and long-term mortality in patients with NSTEMI in order to select the most favorable treatment strategy. Methods. 101 patients with TTS hospitalized in four centers of invasive cardiology in Podlaskie Voivodeship during the period 2008–2012 were included in the study. The patients were divided into two groups: I—52 patients (GRACE ≤ 140 points) and II—49 patients (GRACE > 140 points). Results. The mean GRACE score in the study group was 138.66. The in-hospital stay of Takotsubo in the patients with higher GRACE scores was associated with higher incidence of pneumonia (36.7% vs 7.69%, p=0.0004), rhythm abnormalities (17.3% vs 3.85%, p=0.026), and serious complications (cardiogenic shock, pulmonary edema, and sudden cardiac arrest) (30.6% vs 5.77%, p=0.001). The mean observation period was 7.2 years. A significantly higher risk of 6-month (18.37% vs 3.85%, p=0.019), 1-year (22.45 vs 3.85%, p=0.005), 3-year (40.82 vs 3.85%, p<0.0001), 5-year (42.86% vs 3.85%, p<0.0001), and 7-year mortalities (53.06% vs 9.62%, p<0.0001) was observed in the group of patients with a GRACE score ≥140. At multivariate analysis including low BMI, low eGFR, and a higher GRACE score, all these factors were independent predictor of death (p=0.042; p=0.010; p=0.041). The ROC curve presents the discriminatory scores of the GRACE scale for the follow-up prognostication. The area under ROC curve (AUC) for the GRACE scale was 0.805 (95% CI: 0.718–0.892, p<0.0001), with a cut-off value of 153 points, sensitivity of 74%, and specificity of 77% for TTS. Conclusion. The GRACE scale is highly valuable for the prognostication of death risk in patients with TTS in the early and long-term observation.